Pendampingan Membaca Al-Qur’an Dengan Tema Sehari Mengenal Lebih Dekat Bersama Al-Qur’an - Noviyani, Rafiqa; Octarina, Rizqa (Jurnal Pengabdian Masyarakat, 2023)
The problem of this discussion is the low ability to read the Qur'an at MDA Nurul Hikmah Simpang Tonang and can be said to be not fluent. While the spirit and ability to memorize were found to be very good. Based on preliminary observational data, it was found that ten of the memorizers of the Qur'an only four can be said to be good at reading the Qur'an according to the law of tajweed. The purpose of this study is to guide Qur'an memorizers in reading the Qur'an correctly and precisely according to the makharijul letters and the science of tajweed. The research method is studied based on descriptive qualitative research starting from observation and lectures to find out the initial ability as a whole and provide motivation, the tahsin and talqin methods as reading reinforcement and trial and error methods in order to find out the final ability of material delivery and can form a group in understanding the law of tajweed at MDA Nurul Hikmah Simpang Tonang, West Pasaman Regency. The results of this activity show that: 1) there is a significant relationship in the success of reading the Qur'an according to the rules of tajweed to the fluency and enthusiasm of memorizing the Qur'an and it takes a trial and errol method as an acceleration of the ability to understand the laws of tajweed. Of the 18 MDA participants, it was found that 11 children could read the Qur'an better with the provision of accuracy of letters and tajweed knowledge. 2) the method and strategy of delivering the law of tajweed according to the short and long vowels of 2, 4, 5, and 6 vowels emitted from the level of humming, and the level of buzzing and vagueness can stimulate the ability to read the Qur'an faster and better than before for the memorization of the Qur'an